State-dependent monetary policy regimes - Shayan Zakipour-Saber (Queen Mary University of London, School of Economics and Finance, 2019)
Are monetary policy regimes state-dependent? To answer the question this paper estimates New Keynesian general equilibrium models that allow the state of the economy to influence the monetary authority's stance on inflation. I take advantage of recent developments in solving rational expectations models with state-dependent parameter drift to estimate three models on U.S. data between 1965-2009. In these models, the probability of remaining in a monetary policy regime that is relatively accommodative towards inflation, varies over time and depends on endogenous model variables; in particular, either deviations of inflation or output from their respective targets or a monetary policy shock. The main contribution of this paper is that it finds evidence of state-dependent monetary policy regimes. The model that allows inflation to influence the monetary policy regime in place, fits the data better than an alternative model with regime changes that are not state-dependent. This finding points towards reconsidering how changes in monetary policy are modelled.
Keywords: C13; C32; E42; E43; 330; Markov-Switching DSGE; State-dependence; Bayesian Estimation